Breeding population size, migration, and wintering of the Eurasian Siskin Spinus spinus in relation to seed crop sizes of food trees - Dale, Svein; Ekebom, Agneta; Dahl, Åslög (Ornis Svecica, 2025)
Bird species in boreal forests that utilise seed crops from masting trees face large temporal and spatial variation in food availability. Seed crop size is therefore expected to influence breeding population size, migration, and wintering. We analyse ≤36-year time series of Eurasian Siskin Spinus spinus numbers in Sweden in relation to seed crop sizes of Norway spruce Picea abies, Scots pine Pinus sylvestris, birch Betula spp. and alder Alnus spp. Breeding numbers were somewhat positively associated with spruce, birch, and alder seed crop sizes, but peak breeding numbers sometimes also coincided with small crop sizes. Migration was not strongly related to seed crop sizes, but positively associated with breeding population size. Wintering numbers were strongly positively associated with spruce, birch, and alder seed crop sizes. Pine did not affect any Siskin numbers. This suggests that at large spatial and temporal scales, spruce seeds are less important for Siskin breeding than previously thought. Nevertheless, spruce, birch and alder may all have some influence on breeding and were positively associated with wintering numbers, while migration appears to be a density-dependent process rather than a response to lack of food. The results provide a unique insight into how multiple seed crops affect a seed-eating bird.